Pengaruh Pendidikan Dan Tingkat Pengangguran Terhadap Kemiskinan Provinsi Aceh - Nurlina; Puti Andiny; Zainuddin; Jalaluddin; Natasya, Putri (Jurnal Sociohumaniora Kodepena (JSK), 2022)
The purpose of this study was to determine the effect of education, and the unemployment rate on the number of poor people in Aceh Province simultaneously and partially. This study uses secondary data from 2011-2020 using the Eviews program. The analysis technique used is multiple linear regression. Based on the results of the analysis, it was found that education and the unemployment rate simultaneously had a significant effect on the number of poor people. Education partially has a negative and significant effect on the number of poor people, while the unemployment rate partially has a negative and insignificant effect on the number of poor people.